1982
DOI: 10.1177/0013161x82018002007
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Employment: How Extensive is a Teacher's Religious Freedom?

Abstract: Balancing the variety of religious beliefs of teachers and the public schools 'secular purpose poses a difficult problem for educational policy makers. Case law and the constitutional issues related to religious freedom and employment practices are reviewed in this article. Implications for practice and avenues forfurther analysis are suggested on the basis of the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Although religious discrimination continues to be a factor affecting employment conditions, such as leaves of absence, free speech issues, and work attire (Beezer, 1982), the present study indicated that religious affiliation did not appear to influence decisions made during the pre-interview stage of the selection process. Despite the relatively few religious discrimination charges reported to the EEOC (U.S.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although religious discrimination continues to be a factor affecting employment conditions, such as leaves of absence, free speech issues, and work attire (Beezer, 1982), the present study indicated that religious affiliation did not appear to influence decisions made during the pre-interview stage of the selection process. Despite the relatively few religious discrimination charges reported to the EEOC (U.S.…”
Section: Discussioncontrasting
confidence: 72%
“…An exhaustive literature review of social science and legal databases confirmed suspicions about the lack of empirical research on religious discrimination. Specifically, the literature review revealed only one article in which the author examined court cases; the cases focused primarily on religious freedoms of teachers (Beezer, 1982). Beezer' s extensive review covered cases that addressed the impact of teacher employment policies in areas including (a) leave of absence for religious observance, (b) religious beliefs and nature of job, and (c) physical appearance and attire.…”
Section: Religious Discriminationmentioning
confidence: 99%
“…The legal perspective and accountability topic (Topic 13) provides a good example of this pattern. In the 1960s, the articles on this topic mostly discussed an array of issues, namely, the neutrality principle in the U.S. Supreme Court cases dealing with religion and education (see Katz, 1965), church–state relations (see Reutter, 1965), the legal definition of disruptive student behavior (see Ladd, 1971), the significance of the Fourteenth Amendment on public school educators (see La Morte, 1974), school desegregation/integration litigation (see Brown, 1979), and teachers’ religious freedom (see Beezer, 1982). The topic of legal perspective and accountability then tapered off in the 1980s and the 1990s, and then rose again in 2003 with a special issue on law and education.…”
Section: Resultsmentioning
confidence: 99%